2012
DOI: 10.1098/rsif.2011.0726
|View full text |Cite
|
Sign up to set email alerts
|

Computational modelling of cell chain migration reveals mechanisms that sustain follow-the-leader behaviour

Abstract: Follow-the-leader chain migration is a striking cell migratory behaviour observed during vertebrate development, adult neurogenesis and cancer metastasis. Although cell–cell contact and extracellular matrix (ECM) cues have been proposed to promote this phenomenon, mechanisms that underlie chain migration persistence remain unclear. Here, we developed a quantitative agent-based modelling framework to test mechanistic hypotheses of chain migration persistence. We defined chain migration and its persistence based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 32 publications
3
36
0
1
Order By: Relevance
“…Differences in velocity were observed between leading and trailing cells when co-attraction occurred at every 0.1 s or less (see Figure S6, Video S2b). Leading and trailing behaviour has previously been shown to occur in the chick and Xenopus NC [12], [37], [40]. We suggest that this could emerge in a population of identical cells without requiring differentiation of microscopic parameters, as it has been shown for NC migrating in vitro [12].…”
Section: Resultssupporting
confidence: 61%
“…Differences in velocity were observed between leading and trailing cells when co-attraction occurred at every 0.1 s or less (see Figure S6, Video S2b). Leading and trailing behaviour has previously been shown to occur in the chick and Xenopus NC [12], [37], [40]. We suggest that this could emerge in a population of identical cells without requiring differentiation of microscopic parameters, as it has been shown for NC migrating in vitro [12].…”
Section: Resultssupporting
confidence: 61%
“…Other models try to describe collective migration using agent-based models [25]. A study shown by Mi et al [26] models a healing process using an elastic continuum model.…”
Section: Introductionmentioning
confidence: 99%
“…In this paradigm, ‘leader’ cells of NC migratory streams interpret signals from the microenvironment and chart the course for ‘follower’ cells (Wynn et al, 2013, 2012). However, identifying these leader cells genetically has been challenging, perhaps in part due to a dynamic identity and/or shifting population.…”
Section: Migratory Mechanisms and Communicationmentioning
confidence: 99%
“…Several models have been put forward to explain the underlying mechanisms for NC migratory guidance, including leader-follower models (Wynn et al, 2013, 2012), chase-and-run (Theveneau et al, 2013), and contact inhibition of locomotion (CIL) (Carmona-Fontaine et al, 2008). While it is established that NCCs use guidance cues and the local extracellular matrix (ECM) to collectively migrate (Banerjee et al, 2013; McLennan et al, 2010), we lack a thorough mechanistic understanding of NCC collective migration and how it varies between subpopulations of NCCs destined for different locations and fates.…”
Section: Introductionmentioning
confidence: 99%